PENGARUH SPUTTERING TiN TERHADAP KEKASARAN, KEKERASAN PERMUKAAN MATERIAL AISI316L - Jemssy Ronald Rohi; Priyo Tri Iswanto; Tjipto Sujitno; Erich Umbu Kondi (Politeknik Negeri Jakarta, 2019)
AISI 316L is widely used for implantation in orthopedic surgery due to its good corrosion resistance, mechanical properties and low cost. However, AISI 316L is not well suited for biocompatibility with the body, so implant material with AISI 316L can’t be used for a long time. One way to improve the corrosion resistance and mechanical properties of AISI 316L is to perform a surface treatment such as sputtering. This study discusses the effect of deposition sputtering TiN of 60, 90, 120 and 150 minutes on roughness and surface hardness at a ratio of argon gas and nitrogen to 80% Ar:20% N2. The results of the surface roughness value of the TiN sputtering layer deposited to AISI 316L for 60, 90, 120, and 150 minutes were 0.02 μm, 0.04 μm, 0.06 μm, and 0.04 μm respectively. This shows that the coating time of TiN in AISI 316L has no significant influence on value of surface roughness. Surface hardness results at 60, 90, 120, and 150 minutes were obtained with 268 HVN, 275 HVN, 278 HVN and 282 HVN. Increased hardness value, as the TiN thin layer has a higher hardness value compared to AISI 316L. The longer the deposition time, the more layers are formed and the layer becomes thicker. With the thickness of the layer, the density at the grain boundary increases. Because the higher density leads to grain growth, in which form micropores.